Reading Stories Activates Neural Representations of Visual and Motor Experiences. - Speer, Nicole K.; Reynolds, Jeremy R.; Swallow, Khena M.; Zacks, Jeffrey M. (Psychological Science., 2009)
A study used functional neuroimaging to examine how reading stories activates neural representations of visual and motor experiences. Functional neuroimaging revealed how different brain regions track different aspects of a story, such as the physical location of a character or existing goals. Some of these regions reflect those involved when individuals engage in, imagine, or observe similar real-world activities. These findings support the view that readers understand a story by replicating the events in the story world and revising their simulation when features of that world change.